Analisa Keuangan dan Industri Perusahaan Barang Baku Kimia Indonesia - Ade Nahdiatul Hasanah (JOURNAL INTELEKTUAL, 2025)
Introduction/Main Objectives: This study aims to measure the financial performance of chemical companies in Indonesia during the period 2021–2024 using liquidity and solvency ratio analysis, as well as to evaluate the condition and trends of the chemical industry. Background Problems: Chemical companies in Indonesia play a strategic role in meeting the raw material needs of the national industry, ranging from pharmaceuticals to heavy manufacturing. However, global economic fluctuations, environmental pressures, and geopolitical uncertainties pose significant challenges to the financial performance of this sector. Research Methods: This study employs a descriptive quantitative approach, with five chemical companies listed on the Indonesia Stock Exchange (IDX) as research subjects. Secondary data were obtained from annual financial reports (2021–2024). The analysis was conducted by calculating liquidity and solvency ratios and comparing industry trends. Finding/Results: The main findings indicate that companies with stable liquidity ratios and moderate solvency tend to have more resilient profit performance against external pressures. Conclusion: Chemical companies with healthy capital structures and efficient cash management demonstrate superior financial performance